2020
DOI: 10.1177/1179173x20903784
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Risk Perceptions and Cigarette, E-cigarette, and Dual-Product Use Among Canadian Adolescents

Abstract: Introduction: The popularity of e-cigarettes has increased significantly in recent years. E-cigarettes are perceived as less harmful than cigarettes, and both dual-use of cigarette and e-cigarette use is common among adolescents. This study assessed cigarette and e-cigarette risk perception and associations with dual-product use among Canadian adolescents. Methods: We used data from the 2016-2017 Canadian Student Tobacco, Alcohol, and Drugs Survey. Perceived risks of cigarette and e-cigarette use were classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
2
5
1
Order By: Relevance
“…Our findings further revealed that lower perceived harmfulness of e-cigarettes was associated with e-cigarette use daily or some days. These findings are consistent with previous studies (Amrock et al 2016 ; Huang et al 2019 ; Manzione et al 2020 ) that found that a reason for continuous use of e-cigarettes was related mainly to less perceived harmfulness of e-cigarettes. We also found that current cigarette smokers were more likely to engage in e-cigarettes use than were non-cigarette smokers.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings further revealed that lower perceived harmfulness of e-cigarettes was associated with e-cigarette use daily or some days. These findings are consistent with previous studies (Amrock et al 2016 ; Huang et al 2019 ; Manzione et al 2020 ) that found that a reason for continuous use of e-cigarettes was related mainly to less perceived harmfulness of e-cigarettes. We also found that current cigarette smokers were more likely to engage in e-cigarettes use than were non-cigarette smokers.…”
Section: Discussionsupporting
confidence: 93%
“…There is a lack of consensus in the literature about the associations between the perceived health risks of e-cigarettes and their actual use among U.S. adults (Cooper et al 2016 ; Czoli et al 2017 ; Manzione et al 2020 ; Piñeiro et al 2016 ; Popova et al 2017 ; Wackowski and Delnevo 2016 ). Individuals who perceived e-cigarettes as less harmful than actual cigarettes are more likely to use e-cigarettes (Amrock et al 2016 ; Huang et al 2019 ; Manzione et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smokers who perceived IQOS closer in risk to their cigarettes used more SPD, whereas those who perceived IQOS to be less risky than their cigarettes used fewer. This finding appears inconsistent with the literature on tobacco use risk perceptions, where high risk is associated with lower odds of use 26. As novel products enter the market, smokers may have little information to base their perceptions beyond marketing27 and may base risk perceptions on similarities between the novel product and their cigarettes 28.…”
Section: Discussionmentioning
confidence: 73%
“…Research shows that adolescent and young adult (AYA) perceptions of tobacco- and e-cigarette-related health risks are associated with future use of these products (Cooper et al, 2018; Kong et al, 2015; Manzione et al, 2020; Morrell et al, 2010; Song et al, 2009; Strong et al, 2019). These studies are in line with several theories of health behavior.…”
mentioning
confidence: 99%